The Solution for Achieving Ethical Economics: Strengthening the Ethics of Accountants - Wolf, Ruth (Prabandhan: Indian Journal of Management, 2013)
The article refers to accountants as the foundation stone for the preservation of business and ethical stability in companies around the world. Therefore, the article recommends that accountants should be educated in these aspects during the process of their academic training. The main focus of the training should be on the strengthening of their personalities and their ability to withstand pressure. The article emphasizes the main stumbling blocks encountered by accountants in their work, and stresses the importance of writing accounting reports properly and preventing "creative accounting". An accountant's job requires restraint, patience, and the ability to withstand pressure from bosses and clients alike. In line with the necessary training in honesty and integrity of accountants in all cultures and countries, the academia is responsible for training accountants not only to gain knowledge about accounting laws and regulations, but also to help mold their personalities and more.